Rethinking the body in South Asian traditions - Dimitrova, Diana (Routledge series on South Asian culture, 2021)
"This book analyses cultural questions related to representations of the body in South Asian traditions, human perceptions and attitudes toward the body in religious and cultural contexts, as well as the processes of interpreting notions of the body in religious and literary texts. Utilising an interdisciplinary perspective by means of textual study and ideological analysis, anthropological analysis, and phenomenological analysis, the book explores both insider- and outsider perspectives and issues related to the body from the 2nd century CE up to the present-day. Chapters assess various aspects of the body including processes of embodiment and questions of mythologizing the divine body and othering the human body, as revealed in the literatures and cultures of South Asia. The book analyses notions of mythologizing and "othering" of the body as a powerful ideological discourse, which empowers or marginalizes at all levels of the human condition. Offering a deep insight into the study of religion and issues of the body in South Asian literature, religion and culture, this book will be of interest to academics in the fields of South Asian studies, South Asian religions, South Asian literatures, cultural studies, philosophy and comparative literature"--